2017
DOI: 10.1111/anu.12621
|View full text |Cite
|
Sign up to set email alerts
|

Replacing fish meal with vegetable protein sources in feed for juvenile red swamp crayfish, Procambarus clarkii : Effects of amino acids supplementation on growth and feed utilization

Abstract: An 8-week growth trial was conducted to investigate the effects of dietary fish meal replacement with a vegetable mixture of soybean meal and rapeseed meal (1:1) on growth of juvenile red swamp crayfish. Nine isonitrogenous diets were designed: V0, V34, V50, V65, V73 and V81 with six levels of vegetable proteins, and VA48, VA63 and VA78 by further adding crystalline lysine and methionine into V50, V65 and V81.Compared with V0, V34 significantly improved the specific growth rate (SGR), while V65, V73, V81 and V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
1
10
0
1
Order By: Relevance
“…Indeed, we observed the lowest growth rate for the feed with the lowest methionine level. This is consistent with the notion that methionine is a growth-limiting nutrient for marbled crayfish, similar to other crayfish, and shrimps and fish (Yan et al, 2007;Gu et al, 2013;Tan et al, 2018). Interestingly, the feed with the highest methionine level mainly promoted growth at earlier developmental stages, while later stages performed best with a feed that had an intermediate methionine level.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Indeed, we observed the lowest growth rate for the feed with the lowest methionine level. This is consistent with the notion that methionine is a growth-limiting nutrient for marbled crayfish, similar to other crayfish, and shrimps and fish (Yan et al, 2007;Gu et al, 2013;Tan et al, 2018). Interestingly, the feed with the highest methionine level mainly promoted growth at earlier developmental stages, while later stages performed best with a feed that had an intermediate methionine level.…”
Section: Discussionsupporting
confidence: 88%
“…Methionine is a limiting amino acid for many animals and its deficiency can directly affect animal growth (Bulbul et al, 2015). Supplementation with crystalline amino acids is therefore required to meet the amino acid demands of aquaculture livestock, including crustaceans (Nunes et al, 2014;Tan et al, 2018). As inadequate protein and feed utilization causes high ammonia production, tailored feeds also contribute to maintaining high water quality (Cowey and Walton, 1989;Council, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from protein, the amino acids and micronutrients must also satisfy decapod's needs in order to lead to good growth performance. The requirements for essential amino acids such as histidine, isoleucine, lysine, leucine, methionine, phenylalanine, threonine, tryptophan, and valine have been established for a number of species such as the kuruma prawn (Marsupenaeus japonicas) [60], sesarmid crab (Episesarma singaporense) [61], river prawn (Macrobrachium americanum) [62], European lobster [63], and red swamp crayfish [64]. Methionine and lysine are most used in the feeding of commercially farmed decapods due to their wide availability, but are limited in plant and rendered animal byproducts [65].…”
Section: Proteinmentioning
confidence: 99%
“…The dietary protein and lipid requirements for red swamp crayfish have been determined to be 280-320 g kg −1 diet (Hubbard et al, 1986;Xu et al, 2013) and 40-70 g kg −1 diet (Xu et al, 2013), respectively. Besides, optimal animal protein to vegetable protein ratio in the diet (Tan et al, 2018;Xu et al, 2010), growth and immune improvement effect of dietary polysaccharide supplementation (Liu et al, 2020) have also been investigated in red swamp crayfish. However, few nutritional studies on vitamins for crayfish except the effects of dietary vitamin C on the growth performance, nonspecific immunity and antioxidant capacity were reported (Kong et al, 2021), which indicated that the retention rate of the coated vitamin C after processing is very low.…”
mentioning
confidence: 99%